Influencia del taller LISTEN UP en el desarrollo de la habilidad de listening del idioma inglés de los estudiantes del 4° grado “B” del nivel secundario de la I.E N° 0004 “Túpac Amaru”, Tarapoto - 2013 - Portocarrero Gutierrez, Melissa (2013)
The present research provides an alternative of solution in the development of listening comprehension in the second language in secondary level students of the EBR, employing for that subtitled videos as a methodological strategy. La investigación nace de la dificultad que presentan los alumnos en el proceso de enseñanza aprendizaje de un segundo idioma, en este caso el inglés. En la habilidad de Listening, se refleja la falta de comprensión y discriminación de sonidos en diálogos y canciones; estos problemas surgen debido a la escasa práctica de metodologías que se aplican en el desarrollo del listening, así también el uso inadecuado de material didáctico. The research comes from the difficulty that the students show in the teaching – learning process of a foreign language, for example the English. In the listening ability this is reflected in the lack of comprehension and for recognizing sounds in dialogues or songs; these listening problems appear because of poor methodological practices to develop the listening skills, as well as, the inappropriate use of training materials. The research is based on a behavioral approach of Frederick Skinner (stimulus-organism response-reinforcement) and it is justifiable to sustain with psychological, linguistic, and educational foundations, as well as it has Theoretical value, Practical utility, social relevance for convenience and based on the benefits that generates. Methodologically is focused on the perspective of audio -lingual method. The goal of this research is to implement a pedagogical proposal based on the use of subtitled videos to improve the student’s listening skill. In order to do so, we worked with a group of 26 students of the Educative Institution N° 0004 “Tupac Amaru”. The students were provided with listening video activities with subtitles included. The group watched eight videos with subtitles during eight weeks. At the end of the class, the students answered an exam in order to determine the progress in their Listening ability acquisition of English as a foreign language. After the proposal’s implementation, the results, conclusions and pedagogical issues will be showed.